Development of a RNA profiling assay for biological tissue and body fluid identification. (December 2015) - Chong, Kevin Wai Yin; Wong, Yongxun; Ng, Boon Kiat; Thong, Zhonghui; Syn, Christopher Kiu-Choong
Abstract: Identification of the type of biological tissue or body fluid on forensic samples is no longer limited to conventional biochemical and serological methods. Unlike these methods, RNA profiling allows for 'multiplexing', i.e. concurrent detection of several different biological fluids in a single assay, and is capable of distinguishing between a wider range of forensically relevant biological tissues and body fluids. As such, 24 messenger RNAs (mRNA) and 8 micro-RNAs (miRNA) biomarkers previously identified in literature were screened for their specificities towards blood, saliva, and semen. A total of 15 RNA biomarkers were selected, and subsequently incorporated into a multiplex reverse transcription (RT)-PCR assay for RNA profiling. RNA profiling was then accomplished by capillary electrophoresis of the PCR products, to identify positive identifiers specific to each body fluid type. Based on these positive identifiers, the RNA profiling assay successfully distinguished blood, saliva and semen from each other. This study has also demonstrated that mRNA and miRNA biomarkers can be multiplexed (during the reverse transcription and PCR steps) in a single assay for RNA profiling.